2016
DOI: 10.4028/www.scientific.net/kem.685.162
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Grain Evolution and Dislocation Density during Asymmetric Rolling of Aluminum Alloy 7075

Abstract: The paper gives a mathematical model of grain evolution and dislocation density during asymmetric cold rolling of aluminum alloy 7075 in an SPD mode. Correlations between the effect of equivalent and shear strain on Al 7075 structure are obtained. An agreement of simulation results with experimental data is shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Zerilli et al [ 10 ] proposed Zerilli-Armstrong (ZA) model for face center cubic (FCC) materials based on the thermal activated dislocation motion theory, and the ZA model has been successfully used in high strength steel [ 11 ], 20CrMo [ 12 ], and Ti6Al4V alloy [ 13 ]. Internal state variable model [ 14 , 15 ], Kocks-Mecking (KM) model [ 16 ] and other models [ 17 , 18 ] were proposed to take into consideration of the influence of dislocation and recrystallization. But these models were not unified at different stages (the dynamic recovery stage and the dynamic recrystallization stage), and these models cannot be used in varying strain rates compressions.…”
Section: Introductionmentioning
confidence: 99%
“…Zerilli et al [ 10 ] proposed Zerilli-Armstrong (ZA) model for face center cubic (FCC) materials based on the thermal activated dislocation motion theory, and the ZA model has been successfully used in high strength steel [ 11 ], 20CrMo [ 12 ], and Ti6Al4V alloy [ 13 ]. Internal state variable model [ 14 , 15 ], Kocks-Mecking (KM) model [ 16 ] and other models [ 17 , 18 ] were proposed to take into consideration of the influence of dislocation and recrystallization. But these models were not unified at different stages (the dynamic recovery stage and the dynamic recrystallization stage), and these models cannot be used in varying strain rates compressions.…”
Section: Introductionmentioning
confidence: 99%
“…The HRDSR-processed sheet is flat and smooth while the ESR-processed sheet is wavy and uneven ( Figure 2 d). Pesin et al [ 38 , 39 ] showed in the finite element method (FEM) simulation that high shear strain through thickness of the sheet can only be achieved in HRDSR when the friction coefficient between the sample and the surface of the rolls is high, but the high friction can cause material damage and roll wear. Through control of the amount of thickness reduction per pass and the addition of a small amount of lubricant; however, there have been efforts to minimize these problems in the continuous HRDSR mill ( Figure 2 c).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that shear strain plays a critical role in the grain refinement of aluminum alloys processed by asymmetric rolling [15][16][17][18][19][20] and asymmetric cryorolling. The strength of the material continuously increases with increasing the applied shear strain.…”
Section: Introductionmentioning
confidence: 99%